Family-based genome-wide association studies. (February 2009) - Benyamin, Beben; Visscher, Peter M; McRae, Allan F
In the last 2 years, the effort to identify genes affecting common diseases and complex traits has been accelerated through the use of genome-wide association studies (GWAS). The availability of existing large collections of linkage data paved the way for the use of family-based GWAS. Although most published GWAS used population-based designs, family-based designs have played an important role, particularly in replication stages. Family-based designs offer advantages in terms of quality control, the robustness to population stratification and the ability to perform genetic analyses that cannot be achieved using a sample of unrelated individuals, such as testing for the effect of imprinted genes on phenotypes, testing whether a genetic variant is inherited or de novo and combined linkage and association analysis.